2018
DOI: 10.1038/s41598-018-35345-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Repeated Sprint Ability test on the muscle contractile properties in elite futsal players

Abstract: The aim of this study was to evaluate the effect of a repeated sprint ability (RSA) test on the contractile properties of the muscles in elite futsal players. A total of 20 elite players completed the RSA test (7 × 30 m), and the contractile response from the rectus femoris (RF) and biceps femoris (BF) of both legs were analysed pre and post through tensiomyography. There was a significant increment in 30-m times from the third sprint onwards (p < 0.05). The percent decrement in sprint ability (RSADEC) with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
1
28
1
4
Order By: Relevance
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 67%
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 67%
“…However, few studies have measured the mechanical power alongside the physiological parameters of these athletes [8,10]. Although some have investigated distinct perspectives on repeated sprint ability [43][44][45], few have conducted RAST and calculated its derived mechanical parameters [8,10,46]. Moreover, despite the relevance of agility for futsal athletes already being described [2,47,48], we provide original data based on RAST 2 × 17.5 parameters and agility performance.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated Sprint Ability (RSA) tests are considered as one of the main instrument to analyze the ability of futsal athletes to deal with repeated high-intense actions (Barbero-Alvarez et al, 2008;Sánchez-Sánchez et al, 2018). This test has proved to be useful to analyze the effect of resting between seasons in futsal players (Njororai, 2007) and to discriminate between playing level as those with lower performance decrease in the RSA test showed a higher number of high intensity actions during a real game situation (Carling et al, 2012).…”
Section: Introductionmentioning
confidence: 99%